Partial differential equation models in the socio-economic sciences - Burger, Martin; Caffarelli, Luis; Markowich, Peter A.; et al. (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2014)
© 2014 The Author(s) Published by the Royal Society. All rights reserved. Mathematical models based on partial differential equations (PDEs) have become an integral part of quantitative analysis in most branches of science and engineering, recently expanding also towards biomedicine and socio-economic sciences. The application of PDEs in the latter is a promising field, but widely quite open and leading to a variety of novel mathematical challenges. In this introductory article of the Theme Issue, we will provide an overview of the field and its recent boosting topics. Moreover, we will put the contributions to the Theme Issue in an appropriate perspective.
WWU::100102